2022
DOI: 10.1039/d2cc02544b
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvents coupled with (NH4)3H6CoMo6O24trigger aerobic oxidation of 5-hydroxymethylfurfural to 5-formyl-2-furancarboxylic acid

Abstract: An Anderson-type polyoxometalate (NH4)3H6CoMo6O24 in deep eutectic solvents exhibited outstanding catalytic performance for the selective aerobic oxidation of HMF to FFCA. It is potentially a promising and highly environmentally friendly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Electrocatalytic conversion of biomass-derived chemicals to value-added products offers a promising strategy to realize green polymer chemistry. 1–4 As one of the topmost starting platform molecules, 5 5-hydroxymethylfurfural (HMF) can be oxidized into diverse products, including 2,5-diformylfuran, maleic anhydride, 5-hydroxymethyl-2-furancarboxylic acid, and 2,5-furandicarboxylic acid, etc. 3 Among them, 2,5-furandicarboxylic acid (FDCA) is attractive because it can be used as the monomer for the synthesis of poly(ethylene 2,5-furandicarboxylate) with less CO 2 emissions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrocatalytic conversion of biomass-derived chemicals to value-added products offers a promising strategy to realize green polymer chemistry. 1–4 As one of the topmost starting platform molecules, 5 5-hydroxymethylfurfural (HMF) can be oxidized into diverse products, including 2,5-diformylfuran, maleic anhydride, 5-hydroxymethyl-2-furancarboxylic acid, and 2,5-furandicarboxylic acid, etc. 3 Among them, 2,5-furandicarboxylic acid (FDCA) is attractive because it can be used as the monomer for the synthesis of poly(ethylene 2,5-furandicarboxylate) with less CO 2 emissions.…”
mentioning
confidence: 99%
“…6 The US Department of Energy has listed it amongst the top 12 chemicals. 5 Currently, the oxidation of HMF to produce FDCA generally needs high temperature and pressure, organic solvents, gaseous O 2 , and heterogeneous catalysts, 7,8 making this process less economical along with the formation of by-products. In such circumstances, a more efficient synthetic route is still being explored.…”
mentioning
confidence: 99%
“…In Figure 3A, the peak at 922 cm −1 is ascribed to the symmetric telescoping vibration of terminal M=O in IMo 6 catalyst [37,38] . After being treated with DESs, the peak shifted to 903 cm −1 , suggesting an electron‐donating behavior might happen from DESs to POM [25] . In the following, X‐ray photoelectron spectroscopy (XPS) was utilized to further study the chemical state of Mo in POM and the DESs‐treated POM samples.…”
Section: Resultsmentioning
confidence: 99%
“…The utilization of binary DESs for the catalytic oxidation of HMF has proved its effectiveness. However, the elucidation of the underlying reaction mechanism still demands unwavering dedication from researchers to achieve unparalleled refinement [25] …”
Section: Introductionmentioning
confidence: 99%
“…It was also found that increasing the O 2 pressure and the concentration of NaOH was conducive to the selective formation of FFCA. In a later report, Sun et al [167] developed an Anderson-type polyoxometalate (NH 4 ) 3 H 6 CoMo 6 O 24 and deep eutectic solvents (DESs), which showed excellent HMF oxidation performance. The DESs could break the initial hydrogen bonds and promote the formation of new hydrogen bonds.…”
Section: Selective Oxidation Of Hmf To Ffca Via Hmf-hmfca-fdca Pathwaymentioning
confidence: 99%